A nostálgica viagem no tempo em "Meia Noite em Paris" (Woody Allen, 2011) - Biffi, Luciana Angelice (2018)
The contact with Woody Allen's work 'Midnight in Paris' (2011), opens us to a series of questions that can be problematized and approached in the scope of historiographic research. The relationship of the city of Paris and the artistic production of the 1920s presented in the film are imbued with a certain perception of art and time. From the past / present dynamics, also used as a narrative resource, it’s possible to think of a series of developments in relation to the theme of time, the canon of art and also to understand the way that Allen interprets this themes. In this light, the choices of the director's repertoire extend to the most diverse artistic languages, concentrated in the 1920s in Paris, emphasized in painting and north american literature. From the construction of the main characters, contemporary to us, it is possible to notice different relationships with time, leaving us themes like: nostalgia, anachronisms, 'Golden Age' and time travels that catch the attention of the viewer and historians, who speculates about time. Thus, the research seeks to understand these issues from an interpretative bias of language, in form and artistic content, analyzing some representations and interpreting the dilemmas related to time, in the years 1920 and 2011, dialoguing with historiography and seeking to reflect on the impossibility od denying the present. Key Words: Woody Allen, Paris, Time, Nostalgia, 1920’s